Efficacy of management schedules against gram pod borer, Helicoverpa armigera in chickpea - Yadav, P C; Swaminathan, R; Yadav, S K; Dangi, N L (Indian Journal of Plant Protection, 2020)
Field experiments were conducted during Rabi 2012-13 and 2013-14 at Instructional farm, Maharana Pratap University of Agriculture and Technology, Udaipur, Rajasthan to evaluate the efficacy of nine management schedules against Helicoverpa armigera. The data revealed that all the management schedules were significantly superior to untreated control during both the years. The pesticidal schedule M9 (comprising three sprays of flubendiamide 480 SC @ 200 ml/ha) was most effective in reducing the H. armigera larval population on chickpea; however, it was found to be at par with biointensive module M1 (comprising three spray of HaNPV 250 LE @ 250 ml/ha). Next effective modules were M6 (comprising first spray of HaNPV 250 LE @ 250 ml/ha followed by two sprays of flubendiamide 480 SC @ 200 ml/ha) and M7 comprising first spray of flubendiamide 480 SC @ 200 ml/ ha followed by two sprays of HaNPV 200 LE @ 250 ml/ha. These schedules were statistically at par with each other. The minimum reduction of H. armigera was recorded in M2 (comprising three sprays of Btk 8 l @ 1l/ha).